Adherence to the Mediterranean dietary pattern and heart rate in the SUN project. (29th August 2020) - García-López, M; Martínez-González, MA; Basterra-Gortari, FJ; Barrio-López, MT; Gea, A; Beunza, JJ
Abstract: Background: A higher heart rate has been related to an increase of total and cardiovascular mortality. The aim of this study was to assess the relation between adherence to the Mediterranean diet and heart rate. Design: The SUN project is an ongoing multipurpose cohort study based on university graduates from Spain. Methods: This cross-sectional study included 15, 863 participants of the SUN project. Adherence to the Mediterranean dietary pattern was assessed through a validated 136-item food frequency questionnaire and calculated according to the 9-point score proposed by Trichopoulou. Multiple linear regression models were fitted to assess the relationship between adherence to the Mediterranean dietary pattern and heart rate and 95% confidence intervals were calculated. Results: The multivariable-adjusted models revealed that participants with a high adherence (7–9 points) to the Mediterranean dietary pattern had a heart rate 2.2 bpm (95% CI 1.4–3.1) lower than participants with a low adherence (0–2 points). Conclusions: Adherence to the Mediterranean dietary pattern seems to be related to a lower heart rate